Splitting : a case of female masculinity - Stoller, Robert J. (Yale University Press, 1997)
This classic book is a detailed case study of a woman, otherwise intelligent and apparently sane, who was convinced that she had internally a full set of functioning male sex organs. Dr. Robert Stoller's account of this woman's diagnosis and treatment is illustrated by excerpts from the patient-analyst dialogue during her therapy, providing enough detail to be useful to clinicians in training. Originally published in hardcover in 1973, the book is now available in paperback for the first time."One of the longest, most minutely detailed, and most fascinating case reports in the psychiatric literature. ... An extremely original contribution to the study of perversion."--Ethel Spector Person, M.D., from the Foreword"One of the great clinical case studies. Splitting demonstrates the power of psychoanalytic reasoning in the twentieth century."-Gilbert Herdt, University of Chicago